ANALISIS PENINGKATAN PENDAPATAN MENGGUNAKAN PENTAHO BI BERBASIS DATA WAREHOUSE (STUDI KASUS DI SUNSET EVENUE) - Artana; Eka.pratama (Prodi Sistem Informasi FST Universitas Jambi, 2023)
Analysis of increasing income is the main requirement thing to do for company evaluation, both in terms of marketing and employee performance, this study aims to make a monthly income increase report in the Sunset Evenue case study in Badung Regency which still uses manual methods to control the increase of monthly income. The solution to the existing problem is to use open source Pentaho BI to create the reports for easier analyze. Two-dimensional data will be made multi-dimensional design to facilitate the application of data warehouse design and system design that has been made.